2019
DOI: 10.1080/15323269.2019.1586286
|View full text |Cite
|
Sign up to set email alerts
|

Tablet Computer Use at the Bedside in a New Patient/Family Education Program

Abstract: This article discusses various educational interventions implemented in a new patient/family education program at the University of South Alabama Children's & Women's Hospital in Mobile, Alabama, for patients and family members of those newly diagnosed with pediatric cancer and other chronic illnesses. Tablet computers were made available to access reputable, easy to understand health resources during the educational processes upon diagnosis and continued treatment at the hospital. MedlinePlus, Patient Educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…It is interesting to note that those who knew quite a bit or completely about the condition, procedure or care totaled 36% but there was 92.6% agreement that the videos did help in the comprehension of the topic. The data from the previous project also confirmed that this educational modality is effective and improves comprehension of information and should be incorporated as an effective intervention in patient education (1). This intervention addresses low literacy issues and engages the patient in e-learning.…”
Section: Video Efficacymentioning
confidence: 65%
See 4 more Smart Citations
“…It is interesting to note that those who knew quite a bit or completely about the condition, procedure or care totaled 36% but there was 92.6% agreement that the videos did help in the comprehension of the topic. The data from the previous project also confirmed that this educational modality is effective and improves comprehension of information and should be incorporated as an effective intervention in patient education (1). This intervention addresses low literacy issues and engages the patient in e-learning.…”
Section: Video Efficacymentioning
confidence: 65%
“…With the increased number of hospital units involved in this project, data was needed to determine if the tablets and resources would be as effective as in the previous study with fewer units. To evaluate the efficacy of the interventions and resources used and the usage patterns of all the units involved, the same survey instruments were used (1). The survey, however, would be completed online using a web based application called REDCap instead of a paper version.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations